2001
DOI: 10.1106/lr91-0e0f-k1v0-3m89
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Gentamicin Impregnated Polylactic Acid Beads Implanted in Sheep

Abstract: The biocompatibility and levels of gentamicin released from a poly(lactic acid) (PLA) polymer system in the serum, milk and tissue of a food animal model were determined. Microsphere particles of PLA containing 6.7% (w/w) gentamicin were compressed into 5 mm beads onto suture. Three groups of three cull ewes each were implanted with a bead string of PLA/gentamicin in one caudal thigh (muscle) and PLA control beads in the opposite thigh for 2, 4 and 6 months. Milk and serum samples were obtained at regular inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Gentamicine-release testing revealed residual antibiotic release after being 5 years in situ. Gentamicin implants were impregnated in sheep and showed that the system is promising for the treatment of local infections in veterinary patients …”
Section: Major Fields Of Applications Of Antimicrobial Polymersmentioning
confidence: 99%
“…Gentamicine-release testing revealed residual antibiotic release after being 5 years in situ. Gentamicin implants were impregnated in sheep and showed that the system is promising for the treatment of local infections in veterinary patients …”
Section: Major Fields Of Applications Of Antimicrobial Polymersmentioning
confidence: 99%
“…Antibiotic-loaded acrylic bone cement, described by Buchholz and Engelbrecht [1], is a well-established tool in the prophylaxis [2,3] and treatment of orthopedic infections [4] in humans and animals [5], with meta-analyses indicating that its use reduces the infection rate [6]. Polymethylmetacrylate -PMMA -is characterized by excellent biocompatibility with low intrinsic toxicity and inflammatory activation [7], but experience has shown that not all antibiotics have the properties necessary for their incorporation in this cement.…”
mentioning
confidence: 99%
“…Several antibiotic-releasing collagen sponges or beads produced from various materials intended for local treatment use are currently being investigated or are already commercially available. 5,6,16 Gentamicin makes up the most frequently studied and clinically applied antibiotic with respect to collagen-based drug delivery systems and, moreover, it has already been approved for clinical use. Gentamicin is suitable for post-operative wound treatment applications since it is highly active against G– and, in high concentrations, against G+ bacteria.…”
Section: Introductionmentioning
confidence: 99%